POST-SOVIET CHANGES IN SAMARKAND MUSEUMS - Salimova Kamila Zamirovna (Modern American Journals, 2025)
This article explores the transformations in the museum landscape of Samarkand following Uzbekistan’s independence from the Soviet Union. It examines how these changes reflect broader shifts in national identity, cultural policy, and historical narrative. Drawing on scholarly literature, museum collections, official websites, and news sources, the study categorizes the main institutional, architectural, and ideological developments that have shaped museum practices in the post-Soviet period. It highlights the growing emphasis on national heritage, the marginalization of minority histories, and the role of modernization and state investment in redefining cultural memory. The findings demonstrate how museums in Samarkand have become key instruments in the construction of a new national identity and collective memory in independent Uzbekistan.
Keywords: Samarkand, museums, post-Soviet Uzbekistan, cultural heritage, national identity, collective memory